Concise synthesis of 3-alkylthieno[3,2-b]thiophenes; building blocks for organic electronic and optoelectronic materials - (:unkn) unknown (ROYAL SOC CHEMISTRY, 2019)
Four step synthesis of 3-alkylthieno[3,2-b]thiophenes in the literature was reduced to two steps in good yields, through the preparation of the mono ketone, i.e. 1-(thiophene-3-ylthio)alkan-2-one, from 3-bromothiophene and ring formation reaction. This convenient method provides an easy access with good yields to the preparation of 3-alkylthieno[3,2-b]thiophenes, which are important materials for organic electronic and optoelectronic applications. SEM, AFM and contact angle (CA) analyses of their electropolymers on indium tin oxide (ITO) indicated that as the alkyl chains became longer, the polymers provide a more hydrophobic layer with CA up to 107 degrees.
Keywords: PHOTOVOLTAIC PROPERTIES; CONJUGATED POLYMERS; SEMICONDUCTORS; THIOPHENE; MOBILITY; DONOR; UNITS